UPAYA YANG DILAKUKAN POLRES BADUNG DALAM PENERBITAN SURAT KETERANGAN CATATAN KEPOLISIAN (S.K.C.K) TERHADAP MANTAN NARAPIDANA - Putu Yunika Sulistyawati (Kerta Dyatmika, 2019)
Police Registration Certificate (SKCK) is a letter issued by the police explaining that the applicant has never had a legal error as a condition of applying for work in government agencies or others. The aim is to find out a person's legal history, and to ensure that anyone who has had a legal problem will be recorded in a police record, which can indirectly result in his reputation being considered. The problems discussed in this study are about how the effectiveness of the issuance of police records (SKCK) against former naapidana in Badung Police Station and What are the obstacles faced by the Badung police station in the issuance of police records (SKCK) for former naapidana The methodology of this research is empirical research with direct interviews to those who are competent to answer the problem formulation about the efforts and constraints of the issuance of police records (SKCK) on ex-naapidana in Badung Regional Police, which are based on data collection techniques by making direct observations or observation and analyze the applicable legislation, library materials, literature and scientific studies from scholars relating to the problem being examined, whether sourced from primary, secondary or tertiary legal material.Based on the results of the study showed that the issuance of SKCK in Badung Regional Police always tried to meet the expectations of the community, this can be seen from the efforts of the Badung Regional Police Satintelkam in its efforts to improve the quality of existing services by knowing the desires and needs of its customers by providing media or means as a tool to submit complaints and customer expectations are routinely held evaluations to improve service quality and to achieve public satisfaction. Keywords: inmate, SKCK.